Primary Care Screening, Brief Intervention, and Referral to Treatment for Adolescent Substance Use in Lebanon: A National Cross-sectional Study. (March 2021) - Alayan, Nour; Naal, Hady; Makhoul, Melissa; Avedissian, Tamar; Assaf, Ghada; Talih, Farid; Hamadeh, Randa
Introduction: Substance use among adolescents is on the rise globally. Adolescents rarely seek help for problematic substance use and healthcare professionals can easily fail to identify adolescents with risky substance use. There is therefore a significant global need for substance use screening by healthcare professionals followed by appropriate intervention. Screening, brief intervention, and referral to treatment (SBIRT) is an evidence-based practice that enables clinicians to determine adolescents' risk for substance use and intervene accordingly. However, little effort has been placed on empowering primary care clinicians to use it in Lebanon. We explored the attitudes, perceptions, and practices of primary care nurses and physicians regarding adolescent SBIRT use. Methods: The study used a cross-sectional multisite survey design targeting urban and rural areas in Lebanon. A national sample of 140 physicians and nurses was recruited using random sampling stratified by governorate. Participants completed mailed or online surveys addressing their practices, attitudes, role perceptions, and self-efficacy regarding SBIRT use. Results: This study revealed that 57.8% of healthcare professionals were not familiar with the SBIRT model and that 76.2% did not practice SBIRT in their setting. The majority addressed the problem of substance use through educating and counseling adolescents about the dangers of substance use (84.2%) and encouraged them to stop (82%) but only 2% reported using standardized instruments for substance use screening. Most participants (88.1%) reported their willingness to use SBIRT in their clinical practice and 92.4% expressed an interest in receiving SBIRT training. Overall, the results showed positive attitudes ( M = 4.38, SD = 0.89) and role responsibility ( M = 4.47, SD = 1.62) toward addressing substance use in adolescents, in addition to a high level of perceived self-efficacy in addressing substance use ( M = 4.04, SD = 0.92). Our results showed minimal differences between nurses' and physicians' perceptions and self-efficacy regarding SBIRT use. Conclusions: Our study confirms the lack of a standardized approach toward adolescent substance use screening and intervention by primary healthcare providers in Lebanon but revealed the readiness and willingness to receive training and proper support to adopt an evidence-based approach such as SBIRT.